the ANALYSIS OF THE EFFECT OF PREMIUM PRICES AND GREEN PRODUCT QUALITY ON CONSUMER SATISFACTION WITH PURCHASING DECISIONS AS INTERVENING VARIABLES - andreansyach, muhammad david (Study of Scientific and Behavioral Management, 2024)
ABSTRACT This study aims to determine the effect of premium price variables (X1) and green product quality (X2) on consumer satisfaction (Y) with purchasing deci sions as intervening variables (Z). This study uses a type of quantitative research by reviewing the results of respondent questionnaire data as many as 108 respondents and carried out in October 2023, the population of consumer data recorded in consumer books in galleries and using purposive sampling techniques is processed with SPSS. The results of this study show that premium prices have no effect on consumer satisfaction, the quality of green products does not affect consumer satisfaction, consumer decisions have a significant positive effect on consumer satisfaction, premium prices have a significant positive effect on purchasing decisions, and the quality of green products affects purchasing decisions in Bengok Craft consumers Keywords: premium price, green product quality